Production at the leading edge of technology Proceedings of the 9th Congress of the German Academic Association for Production Technology (WGP), September 30th - October 2nd, Hamburg 2019 - Wulfsberg, Jens Peter; Hintze, Wolfgang; Behrens, Bernd-Arno (Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2019)
The focus of the Congress will be leading-edge manufacturing processes. Topics include manufacturing at extreme speed, size, accuracy, methodology, use of resources, interdisciplinarity and more. Contributions from production and industrial engineering are welcome. Challenges from the areas of manufacturing, machines and production systems will be addressed. Production research constantly pushes the boundaries of what is feasible. The Congress "Production at the leading edge of technology" will highlight production processes that are advancing into areas that until recently were considered unfeasible, also in terms of methodology, use of resources and interdisciplinarity. But where does the search for new limits lead? Which limitations do we still have to overcome, which ones do we not want to overcome? The aim of the German-speaking colloquium is to establish connections between the research locations and to intensify the overall transfer of results and experience with industrial users.